Teaching with research from the Programa Ciência na Escola-PCE as a tool for continuing education in schools in the countryside of the State of Amazonas (Research, Society and Development, 2021)
In this article we aim to analyze the Science at School Program (PCE) as a continuing education for teachers and a program to encourage scientific initiation in the Amazon context. We intend to announce the advances, setbacks, challenges and possibilities with regard to the PCE since its offer and implementation, focusing specifically on schools linked to the Department of Education and Teaching Quality of the State of Amazonas at the current juncture. Based on a critical-reflexive perspective, we place the debate in the field of teacher researcher theory as the need for research to be part of the teaching work, articulating with broader issues that consider solid training as the right of the education professional, indispensable for the professional development of teachers , relating it to the advancement of Scientific Education in the State of Amazonas and the scope of the peasant reality in this process. The study is the result of theoretical and documentary research, based on the survey of notices and selection processes in the last three years, as well as a critical analysis of the real participation of rural school projects in this process and the inclusion of fields in transformative practices.